Sub-parsec resolution cosmological simulations of star-forming clumps at high redshift with feedback of individual stars. Issue 4 (3rd September 2022) - Calura, F; Lupi, A; Rosdahl, J; Vanzella, E; Meneghetti, M; Rosati, P; Vesperini, E; Lacchin, E; Pascale, R; Gilli, R
ABSTRACT: We introduce a new set of zoom-in cosmological simulations with sub-pc resolution, intended to model extremely faint, highly magnified star-forming stellar clumps, detected at z = 6.14 thanks to gravitational lensing. The simulations include feedback from individual massive stars (in both the pre-supernova and supernova phases), generated via stochastic, direct sampling of the stellar initial mass function. We adopt a modified 'delayed cooling' feedback scheme, specifically created to prevent artificial radiative loss of the energy injected by individual stars in very dense gas ( n ∼ 10 3 –10 5 cm −3 ). The sites where star formation ignites are characterized by maximum densities of the order of 10 5 cm −3 and gravitational pressures P grav /k >10 7 K cm − 3, corresponding to the values of the local, turbulent regions where the densest stellar aggregates form. The total stellar mass at z = 6.14 is 3.4× 10^7 M_, in satisfactory agreement with the observed stellar mass of the observed systems. The most massive clumps have masses of 10^6 M_ and half-mass sizes of ∼100 pc. These sizes are larger than the observed ones, including also other samples of lensed high-redshift clumps, and imply an average density one orders of magnitude lower than the observed one. In the size–mass plane, our clumps populate a sequence that is intermediate between the ones of observed high-redshift clumps and local dSph galaxies.